Evaluation of Schottky barrier source/drain contact on gate-all-around polycrystalline silicon nanowire MOSFET. (April 2017) - Ho, Ching-Yuan; Chang, Yew-Jen
Abstract: Self-aligned nickel salicide of gate-all-around silicon nanowires (GAA Si NWs) MOSFET has been investigated using very-large-scale integration (VLSI) process. The nickel salicide (NiSix ) characteristics including sheet resistance (Rs ), phase transformation and Schottky barrier height (SBH) are discussed via line structures and Schottky diode, respectively. RTA temperature strongly affects Rs of NiSix and related with surface morphology. Below 700 °C, near 4.5 Ω/□ of smooth surface of NiSi Rs is obtained in comparison with 12.6 Ω/□ of NiSi2 at 700 °C. Both forward bias of current-voltage (I-V) and temperature-dependency of activation-energy methods have been used to characterize Schottky barrier height (SBH). For 400 °C RTA sample, the SBH and ideality factor extracted from the forward bias of current-voltage (I-V) method are 0.38 eV and 1.53, respectively. Besides, the SBH extracted from temperature-dependency of activation-energy methods is 2.9 eV. The variation of SBH values are attributed to the thermionic-field emission (TFE) which the interface states and inhomogeneity induce slightly tunneling current. Moreover, various channel lengths of Schottky source/drain contacts of GAA Si NWs MOSFET devices were measured and results demonstrate that enough electrical performances combined with ambipolar behavior are available for future application in logical circuit and non-volatile memory.